Internalisasi Moderasi Beragama Berbasis Kearifan Lokal dalam Pengabdian Kebencanaan: Studi Mahasiswa Hukum UINSU di Aceh Tengah (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The flash floods and landslides in Central Aceh Regency are hydrometeorological disasters resulting from the interaction between natural factors and environmental conditions, such as extreme rainfall and declining ecological capacity due to land-use changes. In this context, community service activities conducted by law students of Universitas Islam Negeri Sumatera Utara function not only as humanitarian responses but also as a medium for social learning in internalizing the values of religious moderation based on local wisdom. This study aims to examine the role of students in disaster response and how these values are internalized through interactions with the Gayo community. This research uses a qualitative approach with a descriptive-participatory design. Data were collected through participatory observation, informal interviews, and documentation during activities in disaster-affected areas, and analyzed through data reduction, presentation, and conclusion drawing. The findings show that these activities contributed to both physical recovery and social-psychological support, including trauma healing. Local wisdom values such as deliberation, mutual cooperation, and social solidarity act as social capital in strengthening community resilience and reflect religious moderation in daily life. Overall, this approach integrates academic knowledge, humanitarian values, and religious moderation while fostering students’ social awareness, empathy, and commitment